Sorção de íons metálicos em carvões ativados pulverizados preparados a partir de diferentes resíduos de materiais vegetais - Lima, Liliane Schier de (2013)
The activated carbons are very versatile materials due its high surface area and large pore distribution, which allows its application in numerous industrial processes. In this work we used alternative raw materials for the production of activated carbons as bracatinga wood, maçaranduba wood, babassu coconut shell, dendê coconut shell, tucumã coconut shell, peach stones, eucalyptus and pine wood. The materials were physically activated with steam and oxygen and were characterized by several methods. Their characteristics were compared to commercial activated carbons as bituminous, lignite, bamboo and two chemically activated carbons with zinc chloride and phosphoric acid. The efficiencies of activated carbons were evaluated in the simultaneous sorption of Cu²+, Cd²+ and Cr6+ in aqueous solution. The sorption parameters such as pH, initial concentration of ions, temperature, time and type of activated carbon were evaluated using a fractional factorial design. The main effects on the results were the initial concentration of metallic ions, the pH and the interaction between them. The best efficiency occurred at high concentrations of metals (30 mg/L) and pH 4 for Cu²+ and Cd²+ and pH 2 for the ion Cr6+. Kinetic study data were best fitted to a model of pseudo-second order sorption which indicated a chemical sorption on the surface of the sorbents. It was also observed the effects of competitiveness between the ions, where in the multicomponent system, the sorption of Cd²+ was suppressed and the sorption of Cr6+ favored in most cases. The equilibrium sorption for the three ions was very fast and occurred within the first few minutes. Through the isotherm was observed that the sorption was favorable for all ions in the multi-component system. The shape of the isotherms and the fit models allowed some suppositions about how is occurring the sorption on the sorbents and also calculating the sorption capacity of each ion in activated carbons. Principal component analyzes were performed seeking the correlation between features of the sorbents and sorption capacity of activated carbons. Activated carbon with a high content of acid groups and low zeta potential showed good efficiency in removing the ion Cr6+. Higher volumes of meso pores also influence the sorption of metal ions. The activated carbons were applied in a real effluent from a metallurgical and showed good performance in the simultaneous removal of ions, opening the perspective of study the cost and benefit.